Association Between Appetite and Sarcopenia in Patients With Mild Cognitive Impairment and Early-Stage Alzheimer's Disease: A Case-Control Study - Kimura, Ai; Sugimoto, Taiki; Niida, Shumpei; Toba, Kenji; Sakurai, Takashi (Frontiers in Nutrition, 2018)
Background: Sarcopenia is frequently seen in patients with mild cognitive impairment (MCI) and early-stage Alzheimer's disease (AD). While appetite loss and physical inactivity, which are also frequently seen in dementia, appear to contribute to sarcopenia, to date, no study has investigated this association. Objective: The aim of this study was to examine factors associated with sarcopenia, including appetite and physical activity, in patients with MCI and early-stage AD. Methods: The study subjects comprised 205 outpatients (MCI, n = 151; early-stage AD, n = 54) who were being treated at the Memory Clinic, National Center for Geriatrics, and Gerontology and had a Mini-Mental State Examination (MMSE) score of 21 or higher. All subjects were assessed for appetite by using the Council on Nutrition Appetite Questionnaire (CNAQ). Confounding variables assessed included physical activity, activities of daily living, mood, body mass index (BMI), nutritional status, and medications. Sarcopenia was defined as low muscle mass and low handgrip strength or slow gait speed. Multivariate logistic regression analyses were performed with adjustment for age, gender, education, and confounding variables to examine the association of sarcopenia with physical activity and appetite. Furthermore, sub-analyses were also conducted to clarify the relationship between CNAQ sub-items and sarcopenia. Results: The prevalence of sarcopenia among the subjects was 14.6% (n = 30). Patients with sarcopenia had lower CNAQ scores (those with sarcopenia, 26.7 ± 3.5; those without, 29.1 ± 2.5). Multivariate analysis showed that BMI (odds ratio [OR], 0.675; 95% confidence interval [CI], 0.534–0.853), polypharmacy (OR, 4.489; 95% CI, 1.315–15.320), and CNAQ (OR, 0.774; 95% CI, 0.630–0.952) were shown to be associated with sarcopenia. Physical activity was not associated with sarcopenia. Of the sub-items of the CNAQ, appetite (OR, 0.353; 95% CI, 0.155–0.805), feeling full (OR, 0.320; 95% CI = 0.135–0.761), and food tastes compared to when younger (OR, 0.299; 95% CI, 0.109–0.818) were shown to be associated with sarcopenia. Conclusions: These results suggest that appetite could be a modifiable risk factor for sarcopenia in patients with MCI and early-stage AD. A comprehensive approach to improving appetite may prove effective in preventing sarcopenia.